Залучення працівників вищих навчальних закладів до інноваційної діяльності як інструмент розвитку творчого потенціалу регіону - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д. (Ways to Improve Construction Efficiency, 2012)
The ways of enhancing the use of the creative potential of employees of higher educational institutions in the innovation on the basis of a scientific innovation center.